High voltage composite positive electrode material and its manufacturing method
Patent Information
- Application Number
- JP2023086548
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-02-14
- Filing Date
- 2023-05-25
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-05-25
Smart Images

Figure 0007644170000003 
Figure 0007644170000004 
Figure 0007644170000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode material for secondary batteries, and more particularly to a high-voltage composite positive electrode material and a manufacturing method thereof, which can effectively improve the electrical properties and cycle life of a high-voltage lithium nickel manganese oxide positive electrode material by coating the surface of the high-voltage lithium nickel manganese oxide positive electrode material with an appropriate amount of lithium vanadium fluorophosphate. [Background technology]
[0002] In recent years, with the continuous improvement of the driving range of electric carriers, the demand for ternary oxide cathode materials has also continued to increase. However, the raw material cobalt element used in ternary oxide cathode materials is a rare and strategic precious metal, and is not suitable for mass production and use. In addition, lithium nickel manganese oxide cathode materials are high-voltage cathode materials that do not contain cobalt elements. Because lithium nickel manganese oxide cathode materials have a high oxidation-reduction potential, their energy density is between ternary oxide cathode materials and lithium iron phosphate. In addition, lithium nickel manganese oxide does not contain cobalt element and has a low nickel content, so it is cheaper than ternary oxides, and therefore it has been widely studied and used in the application of next-generation electric carriers and 3C products.
[0003] However, when conventional lithium nickel manganese oxide positive electrode materials are charged and discharged at high potential, HF (LiPF6 + H2O2HF + LiF + PF3O) generated by LiPF6 and H2O in the electrolyte causes other side reactions on the surface of the positive electrode material, resulting in reduced capacity, rate performance, and cycle life.
[0004] Therefore, how to develop a high-voltage composite positive electrode material and its manufacturing method, which can effectively improve the electrical properties and cycle life of high-voltage lithium nickel manganese oxide positive electrode material through surface modification of the high-voltage lithium nickel manganese oxide positive electrode material, is an important problem that needs to be solved quickly in this technical field. Summary of the Invention [Problem to be solved by the invention]
[0005] The purpose of the present invention is to provide a high-voltage composite positive electrode material and its preparation method. By mixing high-voltage lithium nickel manganese oxide (LNMO) powder and lithium vanadium fluorophosphate (LVPF) powder with a specific particle size and mixing ratio, a high-voltage composite positive electrode material is formed in which the lithium vanadium fluorophosphate powder is coated on the surface of the lithium nickel manganese oxide powder, and the electrical properties and cycle life of the high-voltage lithium nickel manganese oxide positive electrode material can be effectively improved. Lithium vanadium fluorophosphate has excellent conductive performance, high voltage platform, excellent rate performance and cycle life. Therefore, by mixing lithium vanadium fluorophosphate and high-voltage lithium nickel manganese oxide positive electrode material in a certain ratio by dry mechanofusion, and coating the lithium vanadium fluorophosphate on the surface of the high-voltage lithium nickel manganese oxide positive electrode material, the conductive performance of the high-voltage lithium nickel manganese oxide positive electrode material can be effectively improved. In addition, the lithium vanadium fluorophosphate provides a protective effect on the surface of the high-voltage lithium nickel manganese oxide positive electrode material, thereby mitigating the impact of destruction of the material surface caused by the electrolyte.
[0006] Another object of the present invention is to provide a high-voltage composite positive electrode material and a manufacturing method thereof. By mixing the lithium nickel manganese oxide powder and the lithium vanadium fluorophosphate powder in an optimal blending ratio by the dry mechanofusion method, the average particle diameter of the lithium vanadium fluorophosphate powder is smaller than one-tenth of the average particle diameter of the lithium nickel manganese oxide powder, and then mixing at 700 rpm to 3500 rpm for 5 to 10 minutes, the lithium vanadium fluorophosphate powder can be coated on the surface of the lithium nickel manganese oxide powder to form a high-voltage composite positive electrode material. Meanwhile, when the surface coating is performed by the dry mechanofusion method, the temperature in the reaction chamber is maintained at 25°C to 45°C to prevent high temperatures from being generated in the reaction chamber to affect the materials and coating substances. The high-voltage composite positive electrode material formed as above has a simple manufacturing process and is easy to control, and maintains excellent rapid charging performance while maintaining a high capacitance at a high charge / discharge rate (C-rate). Compared with the high-voltage lithium nickel manganese oxide positive electrode material not coated with lithium vanadium fluorophosphate, the high-voltage composite positive electrode material coated with lithium vanadium fluorophosphate of the present invention has a cycle retention rate improved by about 10% at a charge rate of 1 C. In other words, by using lithium vanadium fluorophosphate with a lithium hydroxyphosphate iron structure (tavorite-type structure) to modify the surface of the lithium nickel manganese oxide positive electrode material with a spinel crystal phase structure, the rate performance and cycle life of the lithium nickel manganese oxide positive electrode material can be further improved, and it can be widely used in more applications. [Means for solving the problem]
[0007] In order to achieve the above object, the present invention provides a high-voltage composite positive electrode material comprising a lithium nickel manganese oxide powder and a lithium vanadium fluorophosphate powder. The lithium nickel manganese oxide powder has a first average particle size. The molar ratio of the lithium vanadium fluorophosphate powder to the lithium nickel manganese oxide powder is 0.5 or less, and the lithium vanadium fluorophosphate powder has a second average particle size, which is less than one-tenth of the first average particle size. The lithium vanadium fluorophosphate powder and the lithium nickel manganese oxide powder are mixed by a mechanical method to coat the lithium vanadium fluorophosphate powder on the surface of the lithium nickel manganese oxide powder, thereby forming a high-voltage composite positive electrode material.
[0008] In one embodiment, the molar ratio of the lithium vanadium fluorophosphate powder to the lithium nickel manganese oxide powder is less than or equal to 0.2.
[0009] In one embodiment, the molar ratio of the lithium vanadium fluorophosphate powder to the lithium nickel manganese oxide powder is less than or equal to 0.1.
[0010] In one embodiment, the first average particle size is in the range of 10 μm to 20 μm.
[0011] In one embodiment, the second average particle size is in the range of 0.2 μm to 2 μm.
[0012] In one embodiment, the lithium nickel manganese oxide powder has a spinel crystal structure and has the chemical formula LiNi x Mn (2-x) O4, where x≧0.5.
[0013] In one embodiment, the lithium vanadium fluorophosphate powder has a tavorite-type structure and has the chemical formula LiVPO4F.
[0014] In one embodiment, the mechanical method is a mechanofusion method.
[0015] In one embodiment, the operating temperature of the mechanical method ranges from 25°C to 45°C.
[0016] In one embodiment, the rotation speed of the mechanical method ranges from 700 rpm to 3500 rpm, and the mixing time is from 5 minutes to 10 minutes.
[0017] In order to achieve the above object, the present invention provides a method for producing a high-voltage composite positive electrode material, comprising: step (a) of providing a lithium nickel manganese oxide powder and a lithium vanadium fluorophosphate powder, wherein a molar ratio of the lithium vanadium fluorophosphate powder to the lithium nickel manganese oxide powder is not more than 0.5, the lithium nickel manganese oxide powder has a first average particle size, and the lithium vanadium fluorophosphate powder has a second average particle size, the second average particle size being less than one-tenth of the first average particle size; and step (b) of mixing the lithium vanadium fluorophosphate powder and the lithium nickel manganese oxide powder by a mechanical method to coat the lithium vanadium fluorophosphate powder on the surface of the lithium nickel manganese oxide powder, thereby forming a high-voltage composite positive electrode material.
[0018] In one embodiment, the molar ratio of the lithium vanadium fluorophosphate powder to the lithium nickel manganese oxide powder is less than or equal to 0.2.
[0019] In one embodiment, the molar ratio of the lithium vanadium fluorophosphate powder to the lithium nickel manganese oxide powder is less than or equal to 0.1.
[0020] In one embodiment, the first average particle size is in the range of 10 μm to 20 μm.
[0021] In one embodiment, the second average particle size is in the range of 0.2 μm to 2 μm.
[0022] In one embodiment, the lithium nickel manganese oxide powder has a spinel crystal structure and has the chemical formula LiNi x Mn (2-x) O4, where x≧0.5.
[0023] In one embodiment, the lithium vanadium fluorophosphate powder has a tavorite-type structure and has the chemical formula LiVPO4F.
[0024] In one embodiment, the mechanical method is a mechanofusion method.
[0025] In one embodiment, the operating temperature of the mechanical method ranges from 25°C to 45°C.
[0026] In one embodiment, the rotation speed of the mechanical method ranges from 700 rpm to 3500 rpm, and the mixing time is from 5 minutes to 10 minutes. [Brief description of the drawings]
[0027] [Figure 1] 1 shows a manufacturing flow chart of the high voltage composite positive electrode material of the present invention. [Figure 2A] 1 shows an SEM image of the lithium nickel manganese oxide powder of the present invention. [Figure 2B] 1 shows an XRD diagram of the lithium nickel manganese oxide powder of the present invention. [Figure 3A] 1 shows an SEM image of the lithium vanadium fluorophosphate powder of the present invention. [Figure 3B] 1 shows an XRD diagram of the lithium vanadium fluorophosphate powder of the present invention. [Figure 4] FIG. 2 is a schematic diagram showing the mixing of high voltage composite cathode materials by the mechanofusion method of the present invention. [Figure 5A]1 shows SEM images at different magnifications of a control high voltage lithium nickel manganese oxide cathode material of the present invention. [Figure 5B] 1 shows SEM images at different magnifications of a control high voltage lithium nickel manganese oxide cathode material of the present invention. [Figure 5C] 1 shows SEM images at different magnifications of a control high voltage lithium nickel manganese oxide cathode material of the present invention. [Figure 5D] 1 shows SEM images at different magnifications of a control high voltage lithium nickel manganese oxide cathode material of the present invention. [Figure 6A] 2 shows SEM images at different magnifications of a high voltage composite cathode material of a first embodiment of the present invention. [Figure 6B] 2 shows SEM images at different magnifications of a high voltage composite cathode material of a first embodiment of the present invention. [Figure 6C] 2 shows SEM images at different magnifications of a high voltage composite cathode material of a first embodiment of the present invention. [Figure 6D] 2 shows SEM images at different magnifications of a high voltage composite cathode material of a first embodiment of the present invention. [Figure 7A] 4 shows SEM images at different magnifications of a high voltage composite cathode material of a second embodiment of the present invention. [Figure 7B] 4 shows SEM images at different magnifications of a high voltage composite cathode material of a second embodiment of the present invention. [Figure 7C] 4 shows SEM images at different magnifications of a high voltage composite cathode material of a second embodiment of the present invention. [Figure 7D] 4 shows SEM images at different magnifications of a high voltage composite cathode material of a second embodiment of the present invention. [Figure 8A] 13 shows SEM images at different magnifications of a high voltage composite cathode material of a third embodiment of the present invention. [Figure 8B] 13 shows SEM images at different magnifications of a high voltage composite cathode material of a third embodiment of the present invention. [Figure 8C] 13 shows SEM images at different magnifications of a high voltage composite cathode material of a third embodiment of the present invention. [Figure 8D]13 shows SEM images at different magnifications of a high voltage composite cathode material of a third embodiment of the present invention. [Figure 9] 1 shows charge / discharge test curves at a charge / discharge rate (C-rate) of 0.1 C for a control group of the present invention and for Examples 1 to 3. [Figure 10] 1 shows the change in capacitance at room temperature and at 1C cycle for a control group of the present invention and for Examples 1 to 3. [Figure 11] 4 shows the power energy maintenance rates at room temperature and 1C cycle for the control group of the present invention and Examples 1 to 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] Some exemplary embodiments showing the features and advantages of the present invention are described in detail in the following description. It should be understood that the present invention may have various modifications in different aspects, all of which do not depart from the scope of the present invention, and the description and drawings are used for illustrative purposes in nature, and are not intended to limit the present invention. For example, in the following content of the present disclosure, when a first feature is described as being located on or above a second feature, it is meant to include an embodiment in which the first feature is located directly in contact with the second feature, and also includes an embodiment in which the first feature is not in direct contact with the second feature by placing an additional feature between the first feature and the second feature. Furthermore, overlapping reference numbers and / or symbols may be used in different embodiments of the present disclosure. These overlaps are not used to limit the relationships between the respective embodiments and / or the appearance structures for the purpose of brevity and clarity. In addition, although the numerical ranges and parameters in the broad scope of the present disclosure are approximate, the numerical values are described as precisely as possible in the specific examples. Furthermore, terms such as "first", "second", etc. may be used in the claims to describe different components, but these components should not be limited by these terms, and it should be understood that these components described in the embodiments are indicated by different component symbols. These terms are intended to distinguish between different components. For example, a first component can be referred to as a second component, and similarly, a second component can be referred to as a first component, without departing from the scope of the embodiments. The term "and / or" as used in this manner includes any or all combinations of one or more listed items. Unless otherwise specified in the working examples / operating examples, all numerical ranges, amounts, values, and percentages (e.g., angles, durations, temperatures, operating conditions, amount ratios, and the like percentages, etc.) disclosed herein should be understood to be modified in all embodiments by the terms "about" or "substantially".Accordingly, unless otherwise indicated to the contrary, the numerical parameters set forth in the present disclosure and the appended claims are approximations that may be varied as necessary. For example, each numerical parameter should be construed by applying ordinary rounding rules based on at least the number of significant digits described. In this specification, a range can be expressed as from one endpoint to another endpoint, or between two endpoints. All ranges disclosed herein include the endpoints unless otherwise specified.
[0029] FIG. 1 shows a manufacturing flow chart of the high voltage composite positive electrode material of the present invention. FIG. 2A shows an SEM image of the lithium nickel manganese oxide powder of the present invention. FIG. 2B shows an XRD diagram of the lithium nickel manganese oxide powder of the present invention. FIG. 3A shows an SEM image of the lithium vanadium fluorophosphate powder of the present invention. FIG. 3B shows an XRD diagram of the lithium vanadium fluorophosphate powder of the present invention. In this embodiment, the manufacturing method of the high voltage composite positive electrode material first provides a lithium nickel manganese oxide powder and a lithium vanadium fluorophosphate powder in steps S1 and S2, respectively. As shown in FIG. 2A and FIG. 2B, the lithium nickel manganese oxide powder has an average particle size of 15.13 μm and a specific surface area BET=0.31 (m 2 / g), has a spinel crystal structure and has the chemical formula LiNi x Mn (2-x) O4, where x=0.5. As shown in FIGS. 3A and 3B, the lithium vanadium fluorophosphate powder has an average particle size of 0.78 μm and a specific surface area BET=5.39 (m 2 / g), has a tavorite-type structure, and has the chemical formula LiVPO4F. The lithium vanadium fluorophosphate powder can be produced, for example, by grinding with an automatic grinder or by airflow grinding, but the invention is not limited thereto. In this embodiment, the molar ratio of the lithium vanadium fluorophosphate powder to the lithium nickel manganese oxide powder is 0.5 or less. In another embodiment, the lithium nickel manganese oxide powder has the chemical formula LiNi x Mn (2-x) O4, where 2>X>0.5, and a first average particle size, the first average particle size being in the range of 10μm to 20μm. The lithium vanadium fluorophosphate powder has a second average particle size, the second average particle size being in the range of 0.2μm to 2μm. The molar ratio of the lithium vanadium fluorophosphate powder to the lithium nickel manganese oxide powder is 0.5 or less, and the second average particle size of the lithium vanadium fluorophosphate powder is less than one tenth of the first average particle size of the lithium nickel manganese oxide powder. Then, in step S3, the lithium vanadium fluorophosphate powder and the lithium nickel manganese oxide powder are mixed by a mechanical method. Finally, as shown in step S4, the lithium vanadium fluorophosphate powder can be coated on the surface of the lithium nickel manganese oxide powder to form a high voltage composite positive electrode material.
[0030] FIG. 4 is a schematic diagram showing the mixing of high-voltage composite positive electrode material by the mechanofusion method of the present invention. In this embodiment, the lithium vanadium fluorophosphate powder and the lithium nickel manganese oxide powder are mixed by a dry mechanical method, more specifically, by the mechanofusion method. In the present invention, when the lithium vanadium fluorophosphate powder and the lithium nickel manganese oxide powder are filled in a specific mixing ratio in the chamber C of the mechanofusion mixer, they can be mixed by increasing the mechanical energy and the thermal energy at the same time. In the mechanofusion method, the chamber C rotates at a rotation speed R, and when the press-head H gives high impact energy to the particles, the particles of the lithium nickel manganese oxide powder are completely coated and surrounded by the lithium vanadium fluorophosphate powder, and the powder P of the high-voltage composite positive electrode material can be obtained. The two kinds of particles are fixed inside the chamber C by the centrifugal force generated by rotating the chamber C at the rotation speed R. The powder is temporarily clamped and compressed by an internal press head H fixed to the central shaft. The mixed powder is scraped off at high speed by a scraper S. The clamping compression / scraping (shearing) operation is repeated, and the lithium vanadium fluorophosphate powder and the lithium nickel manganese oxide powder are thermally attached by a mechanofusion operation, thereby mixing the particles to obtain a powder P of a high-voltage composite positive electrode material. Therefore, in the present invention, by mixing the lithium vanadium fluorophosphate powder and the lithium nickel manganese oxide powder by a mechanical method, the lithium vanadium fluorophosphate powder can be uniformly coated on the surface of the lithium nickel manganese oxide powder to form a high-voltage composite positive electrode material.
[0031] In this embodiment, the rotation speed R used in the mechanofusion method is in the range of 700 rpm to 3500 rpm. In one example, the rotation speed R used in the mechanofusion method is set to 700 rpm (the power is set to 10% of the total output power of the motor) and the mixing time is set to 5 minutes, so that a high-voltage composite positive electrode material in which the lithium vanadium fluorophosphate powder is uniformly coated on the surface of the lithium nickel manganese oxide powder can be obtained. In one example, the rotation speed R used in the mechanofusion method is set to 1400 rpm (the power is set to 20% of the total output power of the motor) and the mixing time is set to 5 minutes, so that a high-voltage composite positive electrode material in which the lithium vanadium fluorophosphate powder is uniformly coated on the surface of the lithium nickel manganese oxide powder can be obtained. In one example, the rotation speed R used in the mechanofusion method is set to 2100 rpm (the power is set to 30% of the total output power of the motor), and the mixing time is set to 5 minutes, so that a high-voltage composite positive electrode material in which lithium vanadium fluorophosphate powder is uniformly coated on the surface of lithium nickel manganese oxide powder can be obtained. In one example, the rotation speed R used in the mechanofusion method is set to 2800 rpm (the power is set to 40% of the total output power of the motor), and the mixing time is set to 10 minutes, so that a high-voltage composite positive electrode material in which lithium vanadium fluorophosphate powder is uniformly coated on the surface of lithium nickel manganese oxide powder can be obtained. In one example, the rotation speed R used in the mechanofusion method is set to 3500 rpm (the power is set to 50% of the total output power of the motor), and the mixing time is set to 10 minutes, so that a high-voltage composite positive electrode material in which lithium vanadium fluorophosphate powder is uniformly coated on the surface of lithium nickel manganese oxide powder can be obtained. Of course, the rotation speed R and mixing time used in the mechanofusion method can be adjusted according to the actual application requirements.
[0032] Meanwhile, when the lithium vanadium fluorophosphate powder is coated on the surface of the lithium nickel manganese oxide powder using mechanical force, a high temperature is generated inside the chamber C. To avoid the high temperature from affecting the lithium vanadium fluorophosphate powder, the lithium nickel manganese oxide powder, and the powder P of the high-voltage composite positive electrode material, the operating temperature inside the chamber C is maintained in the range of 25°C to 45°C during the mechanical mixing. The high-voltage composite positive electrode material formed as above has a simple manufacturing process and is easy to control, and maintains excellent fast charging performance while maintaining a high capacitance at a high charge / discharge rate (C-rate).
[0033] The manufacturing process and effects of the high voltage lithium nickel manganese oxide positive electrode material of the present invention will be described in detail below with reference to examples.
[0034] Control group
[0035] Lithium nickel manganese oxide positive electrode material (LNMO Blank) particles formed without the addition of modifying lithium vanadium fluorophosphate powder, i.e., with only lithium nickel manganese oxide powder, are shown in Figures 5A to 5D.
[0036] Example 1
[0037] Average particle diameter 15.13μm, specific surface area BET=0.31(m 2 / g), and 1000g of lithium nickel manganese oxide powder (LiNi 0.5 Mn 1.5 O4, LNMO), and the average particle size is 0.78 μm, and the specific surface area is BET = 5.39 (m 2 1. Provide lithium vanadium fluorophosphate powder LiVPO4F (LVPF) weighing 95 g / g, respectively, with the molar ratio of lithium vanadium fluorophosphate powder to lithium nickel manganese oxide powder being 0.1.
[0038] The lithium nickel manganese oxide powder and the lithium vanadium fluorophosphate powder are mixed by a mechanical method to form a high voltage composite cathode material. The high voltage composite cathode material is fabricated by mixing at a rotation speed of 700 rpm for 5 minutes by mechanofusion method in the operating temperature range of 25°C to 45°C. The resulting high voltage composite cathode material is shown in Figures 6A to 6D.
[0039] Example 2
[0040] The manufacturing process of Example 2 is almost the same as that of Example 1, but in the high-voltage composite positive electrode material of Example 2, the molar ratio of lithium vanadium fluorophosphate powder to lithium nickel manganese oxide powder is 0.25. That is, the high-voltage composite positive electrode material is manufactured by mixing lithium nickel manganese oxide powder:lithium vanadium fluorophosphate powder=1:0.2375 (weight percent) at an operating temperature range of 25°C to 45°C at a rotation speed of 700 rpm by mechanofusion method for 5 minutes. The obtained high-voltage composite positive electrode material is shown in Figures 7A to 7D.
[0041] Example 3
[0042] The manufacturing process of Example 3 is almost the same as that of Example 1, but in the high-voltage composite positive electrode material of Example 3, the molar ratio of lithium vanadium fluorophosphate powder to lithium nickel manganese oxide powder is 0.5. That is, the high-voltage composite positive electrode material is manufactured by mixing lithium nickel manganese oxide powder:lithium vanadium fluorophosphate powder=1:0.475 (weight percent) at an operating temperature range of 25°C to 45°C at a rotation speed of 700 rpm by mechanofusion method for 5 minutes. The obtained high-voltage composite positive electrode material is shown in Figures 8A to 8D.
[0043] In order to test the electrical properties of the high-voltage composite positive electrode materials in Examples 1 to 3, the high-voltage composite positive electrode materials in Examples 1 to 3, conductive additive (acetylene black-Li400), adhesive polyvinylidene difluoride (PVDF), and solvent are mixed, coated on a substrate, and dried to form a positive electrode plate. The weight ratio of the high-voltage composite positive electrode material, conductive additive, and polyvinylidene fluoride is 94:4:2. The negative electrode plate is composed of lithium metal. The electrolyte between the positive and negative electrode plates is composed of 1.0M LiPF6, ethylene carbonate (EC) / ethyl methyl carbonate (EMC) (3 / 7). In this way, the preparation of the test samples in Examples 1 to 3 is completed. In another embodiment, the electrolyte between the positive and negative plates may be composed of 1.150M LiPF6, EC / diethyl carbonate (DEC) / EMC (3 / 3 / 4), 5% fluoroethylene carbonate (FEC), although the present invention is not limited thereto.
[0044] As a control group, a lithium nickel manganese oxide powder (LNMO Blank) to which no lithium vanadium fluorophosphate powder for modification is added is used to form a test sample through the same manufacturing process as in Example 1.
[0045] The test samples of the control group and Examples 1 to 3 are subjected to charge and discharge tests at charge and discharge rates (C-rate) of 0.1C, 1C, 2C, 3C, and 5C, respectively. FIG. 9 shows charge and discharge test curves of the control group and Examples 1 to 3 of the present invention at a charge and discharge rate (C-rate) of 0.1C. Table 1 below compares the charge and discharge test results of the control group, Examples 1, 2, and 3 at a charge and discharge rate (C-rate) of 0.1C. As shown in Table 1, compared with the control group, the capacitance of Examples 1 to 3 is slightly improved, and the discharge efficiency (CE) remains at 90% or more. The capacitance improvement effect of the high-voltage composite positive electrode material is optimal in Example 1, in which the lithium nickel manganese oxide powder:lithium vanadium fluorophosphate powder is 1:0.1 (molar ratio). From this, it can be seen that in the present invention, the lithium nickel manganese oxide powder and the lithium vanadium fluorophosphate powder are mixed by mechanical means with a specific particle size and mixing ratio, so that the lithium vanadium fluorophosphate powder is uniformly coated on the surface of the lithium nickel manganese oxide powder to form an optimized high-voltage composite positive electrode material, which can effectively improve the electrical properties and cycle life of the high-voltage lithium nickel manganese oxide positive electrode material, and has good charge and discharge performance. JPEG0007644170000001.jpg66164
[0046] In addition, the following Table 2 compares the rate performance test results of the control group, Example 1, Example 2, and Example 3 at 1C / 2C / 3C / 5C charge / discharge rate (C-rate). As shown in Table 2, compared with the control group, Example 1 can further increase the capacitance at 1C / 2C / 3C / 5C charge / discharge rate (C-rate). From this, it can be seen that in the present invention, by mixing the lithium nickel manganese oxide powder and the lithium vanadium fluorophosphate powder by a mechanical method with a specific particle size and blending ratio, the lithium vanadium fluorophosphate is coated on the surface of the high voltage lithium nickel manganese oxide positive electrode material, and the electrical properties and cycle life of the high voltage lithium nickel manganese oxide positive electrode material are maintained. As a result, the capacitance of the lithium nickel manganese oxide positive electrode material is improved and has good charge / discharge performance. In particular, under the condition of a higher charge / discharge rate (C-rate), the capacitance of Example 1 is significantly improved compared with the control group, and has good fast charging performance. Lithium vanadium fluorophosphate has excellent conductive performance, high voltage platform, excellent rate performance and cycle life, so that by mixing lithium vanadium fluorophosphate and high voltage lithium nickel manganese oxide positive electrode material in a certain ratio by dry mechanofusion method, and coating lithium vanadium fluorophosphate on the surface of high voltage lithium nickel manganese oxide positive electrode material, it can effectively improve the conductive performance of high voltage lithium nickel manganese oxide positive electrode material, and lithium vanadium fluorophosphate provides a protective effect on the surface of high voltage lithium nickel manganese oxide positive electrode material to mitigate the impact of destruction of the material surface by electrolyte. In other words, when the molar ratio of lithium vanadium fluorophosphate powder to lithium nickel manganese oxide powder is less than or equal to 0.2, the effect of coating lithium vanadium fluorophosphate powder on lithium nickel manganese oxide powder is relatively good, and excessive coating can be avoided. In particular, the high voltage composite positive electrode material formed when the molar ratio of lithium vanadium fluorophosphate powder to lithium nickel manganese oxide powder is 0.1 is more preferable.Of course, in the high voltage composite positive electrode material, the molar ratio of the lithium vanadium fluorophosphate powder to the lithium nickel manganese oxide powder is related to the difference in the average particle size between the two, and can be adjusted according to the actual application requirements, which will not be repeated here. JPEG0007644170000002.jpg74166
[0047] FIG. 10 shows the capacitance change at room temperature and 1C cycle for the control group and Examples 1 to 3 of the present invention. FIG. 11 shows the power retention rate at room temperature and 1C cycle for the control group and Examples 1 to 3 of the present invention. A capacitance test was performed for the control group, Examples 1, 2, and 3 at room temperature and a charge / discharge rate (C-rate) of 1C for multiple cycles. As shown in the figure, at a charge / discharge rate (C-rate) of 1C, the capacitance of Example 1 of the present invention is significantly higher than that of the control group, and the retention rate after 300 cycles was improved by about 10%. From this, in the present invention, the lithium vanadium fluorophosphate with a lithium hydroxyphosphate iron structure (tavorite-type structure) is used to modify the surface of the lithium nickel manganese oxide positive electrode material with a spinel crystal phase structure, so that the rate performance and cycle life of the lithium nickel manganese oxide positive electrode material can be further improved and it can be widely used in more applications.
[0048] In addition, in this embodiment, the lithium vanadium fluorophosphate powder used in the high-voltage composite positive electrode material may contain a small amount of carbon, for example, 1.65wt.% carbon, which is added during grinding by an automatic grinder or airflow grinding, so that the surface of the lithium vanadium fluorophosphate powder is coated with a conductive carbon coating layer, providing good conductive performance; and when the lithium vanadium fluorophosphate powder is coated on the surface of the lithium nickel manganese oxide powder to form the high-voltage composite positive electrode material, the carbon coating layer of the lithium vanadium fluorophosphate powder also provides a protective effect, which can mitigate the damage caused by the electrolyte to the surface of the high-voltage composite positive electrode material. Of course, the present invention is not limited thereto.
[0049] As described above, the present invention provides a high-voltage composite positive electrode material and a manufacturing method thereof. By mixing high-voltage lithium nickel manganese oxide (LNMO) powder and lithium vanadium fluorophosphate (LVPF) powder with a specific particle size and compounding ratio, a high-voltage composite positive electrode material is formed in which lithium vanadium fluorophosphate powder is coated on the surface of lithium nickel manganese oxide powder, and the electrical properties and cycle life of the high-voltage lithium nickel manganese oxide positive electrode material are effectively improved. Since lithium vanadium fluorophosphate has excellent conductive performance, high voltage platform, excellent rate performance and cycle life, by mixing lithium vanadium fluorophosphate and high-voltage lithium nickel manganese oxide positive electrode material in a specific ratio by dry mechanofusion method and coating lithium vanadium fluorophosphate on the surface of the high-voltage lithium nickel manganese oxide positive electrode material, the conductive performance of the high-voltage lithium nickel manganese oxide positive electrode material can be effectively improved, and the lithium vanadium fluorophosphate provides a protective effect on the surface of the high-voltage lithium nickel manganese oxide positive electrode material, mitigating the damage of the material surface caused by the electrolyte. The lithium nickel manganese oxide powder and the lithium vanadium fluorophosphate powder in the optimal compounding ratio are mixed by dry mechanofusion, and since the average particle diameter of the lithium vanadium fluorophosphate powder is smaller than one-tenth of the average particle diameter of the lithium nickel manganese oxide powder, the mixture is mixed at 700 rpm to 3500 rpm for 5 to 10 minutes, and then the lithium vanadium fluorophosphate powder is coated on the surface of the lithium nickel manganese oxide powder to form a high-voltage composite positive electrode material. Meanwhile, when the surface coating is performed by the dry mechanofusion method, the temperature in the reaction chamber is maintained at 25°C to 45°C to prevent high temperatures from being generated in the reaction chamber to affect the materials and coating substances. The high-voltage composite positive electrode material formed as above has a simple manufacturing process and is easy to control, and maintains excellent fast charging performance while maintaining a high capacitance at a high charge / discharge rate (C-rate).Compared with the high-voltage lithium nickel manganese oxide positive electrode material not coated with lithium vanadium fluorophosphate, the high-voltage composite positive electrode material coated with lithium vanadium fluorophosphate of the present invention has a cycle retention rate improved by about 10% at a charge rate of 1 C. In other words, by using lithium vanadium fluorophosphate with a lithium iron hydroxyphosphate structure to modify the surface of the lithium nickel manganese oxide positive electrode material with a spinel crystal phase structure, the rate performance and cycle life of the lithium nickel manganese oxide positive electrode material can be further improved, and it can be widely used in more applications.
[0050] The present invention may be modified in various ways by those skilled in the art, without departing from the scope thereof as defined by the claims. [Explanation of symbols]
[0051] C: Chamber H: second conductive carbon P: Powder R: Rotation speed S: Scraper S1, S2, S3, S4: Process
Claims
1. A high voltage composite positive electrode material comprising a lithium nickel manganese oxide powder and a lithium vanadium fluorophosphate powder, The lithium nickel manganese oxide powder has a first average particle size, a molar ratio of the lithium vanadium fluorophosphate powder to the lithium nickel manganese oxide powder is in the range of 0.1 to 0.5, the lithium vanadium fluorophosphate powder has a second average particle size, the second average particle size being less than one-tenth of the first average particle size; The lithium vanadium fluorophosphate powder and the lithium nickel manganese oxide powder are mixed together by a mechanical method to coat the lithium vanadium fluorophosphate powder on the surface of the lithium nickel manganese oxide powder, thereby forming the high-voltage composite positive electrode material.
2. 2. The high voltage composite cathode material of claim 1, wherein the first average particle size is in the range of 10 μm to 20 μm.
3. 2. The high voltage composite cathode material of claim 1, wherein the second average particle size is in the range of 0.2 μm to 2 μm.
4. The lithium nickel manganese oxide powder has a spinel crystal structure and has the chemical formula LiNi x Mn (2-x) O 4 2. The high voltage composite cathode material of claim 1 , wherein x≧0.
5.
5. The lithium vanadium fluorophosphate powder has a lithium iron hydroxyphosphate structure and has the chemical formula LiVPO 4 2. The high voltage composite cathode material of claim 1 , wherein
6. 10. The high voltage composite cathode material of claim 1, wherein the mechanical method is a mechanofusion method.
7. 7. The high voltage composite cathode material of claim 6, wherein the operating temperature of the mechanical method ranges from 25°C to 45°C.
8. 7. The high voltage composite positive electrode material of claim 6, wherein the rotation speed of the mechanical method is in the range of 700 rpm to 3500 rpm, and the mixing time is 5 minutes to 10 minutes.
9. (a) respectively providing a lithium nickel manganese oxide powder and a lithium vanadium fluorophosphate powder, a molar ratio of the lithium vanadium fluorophosphate powder to the lithium nickel manganese oxide powder being in the range of 0.1 to 0.5, the lithium nickel manganese oxide powder having a first average particle size, and the lithium vanadium fluorophosphate powder having a second average particle size, the second average particle size being less than one-tenth of the first average particle size; (b) mixing the lithium vanadium fluorophosphate powder and the lithium nickel manganese oxide powder by a mechanical method to coat the lithium vanadium fluorophosphate powder on the surface of the lithium nickel manganese oxide powder to form a high voltage composite positive electrode material; A method for producing a high voltage composite positive electrode material, comprising:
10. The method for producing a high voltage composite positive electrode material according to claim 9, wherein the first average particle size is in the range of 10 μm to 20 μm.
11. The method for producing a high voltage composite positive electrode material according to claim 9, wherein the second average particle size is in the range of 0.2 μm to 2 μm.
12. The lithium nickel manganese oxide powder has a spinel crystal structure and has the chemical formula LiNi x Mn (2-x) O 4 10. The method of claim 9, wherein x > 0.
5.
13. The lithium vanadium fluorophosphate powder has a lithium iron hydroxyphosphate structure and has the chemical formula LiVPO 4 10. The method of claim 9, wherein the high voltage composite cathode material comprises:
14. 10. The method of claim 9, wherein the mechanical method is a mechanofusion method.
15. The method for producing the high voltage composite cathode material of claim 14, wherein the operating temperature of the mechanical method ranges from 25°C to 45°C.
16. The method for producing the high voltage composite positive electrode material according to claim 14, wherein the rotation speed of the mechanical method is in the range of 700 rpm to 3500 rpm, and the mixing time is 5 minutes to 10 minutes.
Citation Information
Patent Citations
Positive electrode active material composite for lithium ion secondary battery, positive electrode for lithium ion secondary battery, and lithium ion secondary battery
JP2021131938A